2014
DOI: 10.1002/ijop.12110
|View full text |Cite
|
Sign up to set email alerts
|

The importance of autonomy support and the mediating role of work motivation for well-being: Testing self-determination theory in a Chinese work organisation

Abstract: We examine relations between perceived organisational autonomy support and different types of work motivation and well-being outcomes in 266 teachers from two government schools in China. We hypothesised that greater autonomy support would be associated with more autonomous forms of employee motivation, and that teacher motivation would in turn mediate the effects of autonomy support on indicators of work well-being (i.e., job satisfaction, work stress and physical ill symptoms). Results generally supported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 27 publications
10
81
0
6
Order By: Relevance
“…These needs can be notably thwarted through supervisors' undermining behaviours (e.g., spreading rumours and talking down; Duffy, Ganster, & Pagon, ). In contrast, they are satisfied through supervisors' autonomy‐supportive behaviours (i.e., explain the reasons that justify the achievement of professional tasks, encourage initiative, and take into account workers' needs and opinions; Nie, Chua, Yeung, Ryan, & Chan, ), perceived organizational support (i.e., employees' perceptions of the extent to which their organization cares about their well‐being and values their contributions), and positive feedbacks about the accomplished work.…”
Section: Discussionmentioning
confidence: 99%
“…These needs can be notably thwarted through supervisors' undermining behaviours (e.g., spreading rumours and talking down; Duffy, Ganster, & Pagon, ). In contrast, they are satisfied through supervisors' autonomy‐supportive behaviours (i.e., explain the reasons that justify the achievement of professional tasks, encourage initiative, and take into account workers' needs and opinions; Nie, Chua, Yeung, Ryan, & Chan, ), perceived organizational support (i.e., employees' perceptions of the extent to which their organization cares about their well‐being and values their contributions), and positive feedbacks about the accomplished work.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nie, Chua, Yeung, Ryan, and Chan ( 2014 ) recently studied teachers' motivation in Chinese public schools. They found that teachers who experienced more autonomy support from their supervisors also evidenced more intrinsic motivation and identifi ed regulation in their role as teachers.…”
Section: What Teachers Needmentioning
confidence: 99%
“…Er umfasst Verhaltensbereiche, wie das Beantworten von Fragen und das Anbieten von Wahlmöglichkeiten. Die positiven Effekte von Autonomieunterstützung zeigen sich im Arbeits- (Baard, Deci & Ryan, 2004;Güntert, 2015;Lynch, Plant & Ryan, 2005;Nie, Chua, Yeung, Ryan & Chan, 2015;Williams et al, 2009) und Schulkontext (Hagger & Chatzisarantis, 2015;Sheldon & Krieger, 2007;Vansteenkiste, Simons, Lens, Soenens & Matos, 2005). Auch Studien im Sportkontext zeigen, dass autonomieunterstüt-zendes Verhalten von Sportlehrpersonen mit mehr Motivation, höherem Wohlbefinden und einer größeren Persistenz beim Training einhergeht (Adie et al, 2008;Adie, Duda & Ntoumanis, 2012;Edmunds, Ntoumanis & Duda, 2006;Fenton et al, 2016;How, Whipp, Dimmock & Jackson, 2013).…”
Section: Selbstbestimmungstheorie Und Autonomieunterstützungunclassified